Transboundary Environmental Harm in the Arctic : A Study of Accountability for an Oil Spill - Penttilä, Outi (Helsingfors universitet, 2015)
Latterly, the Arctic has transformed from a peripheral region to an area in the focus of the world, especially in terms of oil drilling. Nonetheless, no international legal instrument has addressed the matter of accountability for transnational oil pollution damage. Consequently, this thesis aspires to evaluate whether the current legal constructions, namely State responsibility, international liability, civil liability regimes and multilateral environmental agreements (MEAs), allow establishing accountability or creating a regime of accountability for transboundary environmental harm that results from hydrocarbon exploitation in the Arctic. Finally, the thesis seeks to systematize the law of accountability for environmental harm by providing an examination of the above mentioned current constructions, understood as layers of international accountability in the present thesis. The first layer, which offers an insight into the law of State responsibility for wrongful acts, naturally focuses on the ILC’s Draft Articles on responsibility of States. Both of the main criteria of State responsibility, meaning the attribution of the conduct and the breach of an obligation, will be assessed. However, it quickly becomes apparent that State responsibility faces severe challenges in terms of establishing accountability for oil pollution damage: the exploitation activities are often carried out by private entities whose conduct may only be attributable to States in rare circumstances. Moreover, the environmental obligations remain vague and thus a breach of them hard to prove. Thereby, State responsibility cannot be effectively resorted to in order to enforce accountability for environmental damage. The second layer, international liability, is based on the ILC’s project on international liability of States for injurious consequences. This prominent project, however, ran into difficulties right from the beginning: it was founded on the idea of strict State liability, something the international community was not ready for. ...